Allium Roseum L. Extract Exerts Potent Suppressive Activities on Chronic Myeloid Leukemia K562 Cell Viability Through the Inhibition of BCR-ABL, PI3K/Akt, and ERK1/2 Pathways and the Abrogation of VEGF Secretion. (2nd January 2017) - Souid, Soumaya; Najjaa, Hanen; Riahi-Chebbi, Ichrak; Haoues, Meriam; Neffati, Mohamed; Arnault, Ingrid; Auger, Jacques; Karoui, Habib; Essafi, Makram; Essafi-Benkhadir, Khadija
ABSTRACT: Use of plant extracts, alone or combined to the current chemotherapy as chemosensitizers, has emerged as a promising strategy to overcome tumor drug resistance. Here, we investigated the anticancer activity of Allium roseum L. extracts, a wild edible species in North Africa, on human Chronic Myeloid Leukemia (CML) K562 cells. The dehydrated aqueous extract (DAE) disturbed the cell cycle progression and induced the apoptosis of K562 cells. Chemical analysis of DAE showed a diversity of organosulfur compounds S-alk(en)yl-cysteine sulfoxides (RCSO) and high amount of allicin, suggesting that such molecule may be behind its antitumor effect. DAE was efficient in inhibiting K562 cell viability. DAE inhibitory effect was associated with the dephosphorylation of the BCR-ABL kinase and interfered with ERK1/2, Akt, and STAT5 pathways. Furthermore, we found that DAE-induced inactivation of Akt kinase led to the activation of its target FOXO3 transcription factor, enhancing the expression of FOXO3-regulated proapoptotic effectors, Bim and Bax, and cell cycle inhibitor p27. Finally, we found that DAE reduced the secretion of vascular endothelial growth factor. Overall, our data suggest that A. roseum extract has great potential as a nontoxic cheap and effective alternative to conventional chemotherapy.